Islamic Religious Education Teachers as Character-Mentoring Agents: Strengthening Early-Adolescent Self-Control in an Indonesian Public Junior Secondary School - PutriHidayah, Mega; Neni (Universitas Islam Negeri Raden Intan Lampung, 2026)
This qualitative descriptive case study examines how Islamic Religious Education (IRE) teachers strengthen self-control among seventh-grade students at State Junior Secondary School 19 Merangin, Jambi, Indonesia. Data were generated through classroom observation, semi-structured interviews, and documentation involving the school principal, the IRE teacher of Class VII C, and seventh-grade students. The findings show that student self-control was moderate and uneven: some students displayed politeness, prayer habits, orderly participation in religious activities, and peer reminders, whereas others showed impulsive speech, limited concentration, classroom joking, emotional reactivity, and difficulty completing tasks. IRE teachers supported self-control through four interconnected roles: religious habituation, moral role modeling, personal guidance, and contextual integration of Islamic values into daily learning. The process was enabled by teacher-parent collaboration, homeroom support, school religious routines, and a respectful school culture, but constrained by limited parental supervision, peer provocation, excessive mobile-device use, unconducive classroom situations, and early-adolescent emotional instability. The study contributes a school-based IRE character-mentoring model that links spiritual habituation, relational pedagogy, and collaborative guidance for sustainable self-regulation development.